The congruence of political parties and multi-level party systems in Latin America: conceptualization and review of some measurement tools - Došek, Tomáš (2013)
The objective of these article is to evaluate different kinds of methodological tools thatmeasure the levels of congruence of the competition within de multi-level party systems, unders- tanding this last one as the levels of similitude that are experimented by the different districts where political parties compete. It starts from the premise that every party system is multi- level because in that system exists competition in different institutional levels (and in different districts simultaneously). The relevance of multi-level appears when national elections and subnational elections dynamics are not necessarily equals, and it is required to overcome the methodological traditional nationalism that it has been experimented until the moment in the research agenda about parties and party systems. The review of the concept of «congruence» is not exhaustive, and it seeks to systematize the contemporary literature to observe de similarities and differences in national and subnational electoral dynamics, and the consequences of the use of each measurement tool for the identified dynamics.